Two new species of the genus Bothropolys Wood, 1862 (Chilopoda: Lithobiomorpha: Lithobiidae) from China - Ma, Hui-Qin; Song, Da-Xiang; Zhu, Ming-Sheng (Entomologica Fennica, 2008)
The present paper deals with two new species of the genus Bothropolys Wood, 1862 (Lithobiomorpha: Lithobiidae), recently discovered in China. Bothropolys stoevi sp. n. was found in Hebei and Shanxi Provinces, and Bothropolys edgecombei sp. n.was found in Sichuan Province.We present a key and distributional map of the Chinese Bothropolys species.